Fortified Fermentation: Improving Microbial Viability and Texture of Egghurt Using Skim Milk Powder - Aziz, Fariz Nurmita; Pascual, Evangeline; Rizqiati, Heni (Diponegoro University, 2025)
This study aimed to evaluate the effect of skim milk powder incorporation on the microbiological, physicochemical, and sensory characteristics of egghurt, a fermented egg-based product. The experiment was conducted using varying skim milk concentrations of 0%, 5%, 10%, 15%, and 20% (w/w). Parameters analyzed included water activity (aw), pH, total lactic acid bacteria (LAB), total microbial count, and sensory attributes. Results showed that increasing skim milk concentration decreased egghurt water activity from 0.954 to 0.934 and slightly increased pH from 5.46 to 5.62, indicating higher total solids and buffering capacity. The total LAB count rose significantly from 5.92 to 7.70 log CFU/mL, while total microbial counts ranged from 8.81 to 9.40 log CFU/mL. Sensory evaluation revealed no significant differences in color, aroma, or flavor across treatments; however, texture improved significantly with skim milk addition, increasing from 2.24 to 3.24 on a 5-point scale. Incorporation of egghurt with up to 20% skim milk powder effectively enhanced its microbial viability, physicochemical stability, and textural quality, while maintaining acceptable overall sensory characteristics. The incorporation of skim milk offers a practical formulation approach to develop stable, nutritious, and consumer-acceptable egg-based fermented products with potential functional food value.